Soluble Sema4D in Plasma of Head and Neck Squamous Cell Carcinoma Patients Is Associated With Underlying Non-Inflamed Tumor Profile - Younis, Rania H.; Ghita, Ioana; Elnaggar, Manar; Chaisuparat, Risa; Theofilou, Vasileios Ionas; Dyalram, Donita; Ord, Robert A.; Davila, Eduardo; Tallon, Luke J.; Papadimitriou, John C.; Webb, Tonya J.; Bentzen, Søren M.; et al. (Frontiers in Immunology, 2021)
Semaphorin 4D (Sema4D) is a glycoprotein that is expressed by several tumors and immune cells. It can function as a membrane bound protein or as a cleaved soluble protein (sSema4D). We sought to investigate the translational potential of plasma sSema4D as an immune marker in plasma of patients with head and neck squamous cell carcinoma (HNSCC). Paired peripheral blood and tumor tissue samples of 104 patients with HNSCC were collected at the same time point to allow for real time analysis. Scoring of the histological inflammatory subtype (HIS) was carried out using Sema4D immunohistochemistry on the tumor tissue. sSema4D was detected in plasma using direct ELISA assay. Defining elevated sSema4D as values above the 95th percentile in healthy controls, our data showed that sSema4D levels in plasma were elevated in 25.0% (95% CI, 16.7%-34.9%) of the patients with HNSCC and showed significant association with HIS immune excluded (HIS-IE) (p=0.007), Sema4D+ve tumor cells (TC) (p= 0.018) and PD-L1+ve immune cells (IC) (p= 0.038). A multi-variable logistic regression analysis showed that HIS was significantly (P=0.004) associated with elevated sSema4D; an association not explained by available patient-level factors. Using the IO-360 nanoString platform, differential gene expression (DGE) analysis of 10 HNSCC tumor tissues showed that patients with high sSema4D in plasma (HsS4D) clustered as IFN- negative tumor immune signature and were mostly HIS-IE. The IC type in the HsS4D paired tumor tissue was predominantly myeloid, while the lymphoid compartment was higher in the low sSema4D (LsS4D). The Wnt signaling pathway was upregulated in the HsS4D group. Further analysis using the IO-360, 770 genes set, showed significant non-inflamed profile of the HsS4D tumors compared to the LsS4D. In conclusion, our data reveals an association between sSema4D and the histological inflammatory subtype.